Experimental and numerical comparisons of self-reacting point absorber wave energy converters in irregular waves. (1st February 2019) - Beatty, Scott J.; Bocking, Bryce; Bubbar, Kush; Buckham, Bradley J.; Wild, Peter
Abstract: An experimental and numerical comparison of the performance of two self-reacting point absorber wave energy converter designs is undertaken for heave motions in irregular waves. The experiments consist of a series of 1:25 scale model tests that feature re-configurable WEC body shapes, a feedback controlled power take-off, and a heave motion constraint apparatus. While both designs have the same float, the first design features a streamlined reacting body and the second design features a damper plate reacting body. A time domain numerical model, validated by the experimental results, is used to extend the comparisons of the designs in terms of power matrices, capture width matrices, and mean annual power production. Results indicate that the wave energy converter design with damper plate produces 41% higher mean annual energy production than the wave energy converter design with streamlined reacting body at a representative location near the West Coast of Vancouver Island, British Columbia, Canada. Highlights: Two self reacting point absorber WEC designs are compared in irregular waves. 1:25 scale physical models of the WECs with feedback controlled PTOs are used. Hydrodynamic and friction coefficients are identified from heave decay results A time domain model is validated by experimental power and dynamic motion results The WEC with damper plate produces 41% more power on average compared to the WEC with a streamlined reacting body.